Myocardial infarction following cannabis induced coronary vasospasm - Gunawardena, Mudalige Don Vajira Malin (BMJ Case Rep, 2014)
Smoking cannabis is a rare cause of myocardial infarction. We report a 29-year-old man who presented with acute coronary syndrome following consumption of a type of cannabis with the street name ‘Kerala Ganja’. KG is smuggled into Sri Lanka from India; it is grown in the south Indian state of Kerala and is much more potent than the local ganja (marijuana). The patient developed dynamic ST-segment elevations in different leads in sequential ECGs, corresponding to different coronary artery territories. Coronary angiogram did not demonstrate evidence of occlusive atherosclerotic disease, but showed slow flow down the left anterior descending artery, which improved with administration of intracoronary nitrates. The patient’s cardiac biomarkers were significantly elevated. A diagnosis was made of vasospasm causing myocardial infarction, most likely to have been triggered by cannabis consumption. We highlight the importance of considering this possible aetiology, particularly in patients with ACS with a susceptible social profile.